Application of Transposon Insertion Sequencing to Agricultural Science - Fabian, Belinda K.; Tetu, Sasha G.; Paulsen, Ian T. (Frontiers in Plant Science, 2020)
Many plant-associated bacteria have the ability to positively affect plant growth and there is growing interest in utilizing such bacteria in agricultural settings to reduce reliance on pesticides and fertilizers. However, our capacity to utilize microbes in this way is currently limited due to patchy understanding of bacterial-plant interactions at a molecular level. Traditional methods of studying molecular interactions have sought to characterise the function of one gene at a time, but the slow pace of this work means the functions of the vast majority of bacterial genes remain unknown or poorly understood. New approaches to improve and speed up investigations into the functions of bacterial genes in agricultural systems will facilitate efforts to optimize microbial communities and develop microbe-based products. Techniques enabling high-throughput gene functional analysis, such as transposon insertion sequencing analyses, have great potential to be widely applied to determine key aspects of plant-bacterial interactions. Transposon insertion sequencing combines saturation transposon mutagenesis and high-throughput sequencing to simultaneously investigate the function of all the non-essential genes in a bacterial genome. This technique can be used for both in vitro and in vivo studies to identify genes involved in microbe-plant interactions, stress tolerance and pathogen virulence. The information provided by such investigations will rapidly accelerate the rate of bacterial gene functional determination and provide insights into the genes and pathways that underlie biotic interactions, metabolism, and survival of agriculturally relevant bacteria. This knowledge could be used to select the most appropriate plant growth promoting bacteria for a specific set of conditions, formulating crop inoculants, or developing crop protection products. This review provides an overview of transposon insertion sequencing, outlines how this approach has been applied to study plant-associated bacteria, and proposes new applications of these techniques for the benefit of agriculture.